Seroprevalence of rhinopneumonitis virus in horses from Peru - Galindo, David (2015)
The aim of this study was to determine the seroprevalence of antibodies against Equine Herpes Virus type 1 (EHV-1) and Equine Herpes Virus type 4 (EHV-4), which causes rhinopneumonitis in horses. Blood samples (n=825) from Peruvian horses older than six months of age, both sexes, identified as racehorses, Peruvian Paso, equitation and criollo, in apparent healthy conditions, were collected for detection of neutralizing antibodies against EHV-1/EHV-4 by virus neutralization test. The 48.9 ± 5.3% (403/825) of the samples had antibodies against EHV-1/EHV-4. Antibody titers ranged from 2 to >256, where 58.5% ranged from 2 to 8, 29.5% from 16 to 64, and 11.9% from 128 to >256. The sex and region of the country did not represent a risk for presenting antibodies against EHV-1/EHV-4.